Using The Picture Comment Method in Senior High School Students: Descriptive Text Writing Skills - Ikhlas, Deno Rahmatul; Ariyani, Amra; Iryani, Neni (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The issue of English learning at public senior high school 2 Palembayan, where students' limited ability to write descriptive texts negatively impacted their overall learning outcomes, sparked this research. Therefore, this research aimed to improve students' ability to write descriptive texts using the picture comment method in senior high school. This research is a classroom action study that employs a qualitative approach. A total of 29 students from class X. IPS2 at public senior high school 2 Palembayan participated in this research. The instruments used to collect data were observation sheets, documentation, and tests. The study analyzed the obtained data using both qualitative and quantitative methods. The research findings from each implemented learning cycle demonstrated a significant increase in students' ability to write descriptive texts in English learning using the picture comment method. In cycle I, the learning outcomes of writing descriptive text obtained by students only reached 62% completion with an average score of 68, while in cycle II, it showed a fairly high increase with an average score of 80 and completion of 86%. Therefore, we can conclude that the picture comment method enhances students' descriptive text writing skills in class X.IPS2 of public senior high school 2 Palembayan.